Integrated Tool for High-Feed Turning - Vasilko, Karol (Manufacturing Technology Journal, 2019)
Machining, mainly turning, si characterised by the highest labour input among the technological methods. This leads to the conditin when, for instance, in line production at hammering power press, which produces forginngs in the stroke of 1 second, tens of lathes follow and their gradual turning with the stroke of tens of seconds up to minutes. Whole history of material machining has been lead with the effort to shorten machining time by the improvement of cutting materials, tool geometry, integration of machining The article based on the method integrates roughing and finishing into one operation and ensures high quality of machined workpiece surface.
Keywords: Turning; Tool geometry; Cutting speed; Surface roughness